Sustainable Development im Nord-Süd-Konflikt: Vom Konzept der Umverteilung des Reichtums zu den Erfordernissen einer globalen Gerechtigkeit - Marmora, Leopoldo (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 1992)
This article explores the relationship between the economic exploitation and ecological disadvantaging of the South by the North. Parallel to traditional debates on disparate shares in the world market, terms oftrade ect., a new line ofconfrontation emerges. Tue question goes: How are costs and destruction brought about by modern industrial civilisation to be shared out? Marmora persues the argument (l) that the pattem of traditional distributional conflicts is not applicable to the new constellation of conflicts and (2) that global polarisation between North and South is unlikely to set in. However, a prerequisite for »sustainable development« is that ecological restructuring in industrialised countries be taclded and that developing countries actively take part in world market operations committing themselves to globally protecting the environment.